Fermentation quality of ensiled crimped faba beans using different additives with special attention to changes in bioactive compounds - Marketta Rinne; Milla M. Leppä; Kaisa Kuoppala; Erja Koivunen; Minna Kahala; Taina Jalava; Juha-Pekka Salminen; Katariina Manni (ELSEVIER, 2025)
Faba bean (Vicia faba L.) is a grain legume that provides possibilities to increase local protein self-sufficiency both as feed and food in areas where possibilities for cultivation of other protein crops are limited. However, full ripening may not be achieved and storage of the moist beans by crimping and ensiling provides an economic alternative to drying, and is well suited for animal feeding. The objectives of the current experiment were to evaluate the effects of moisture content and various silage additives on the fermentation quality, aerobic stability and fate of bioactive compounds of ensiled crimped faba beans in a pilot scale ensiling experiment. Faba beans were combine harvested at moisture level of 443 g/kg and crimped prior to ensiling. The following additive treatments were applied using three replicates: 1) control (CON), 2) two commercial lactic acid bacteria inoculants as mixture (LABmix), 3) In-house LAB inoculant (LABLuke), 4) Formic acid based product (FA) and 5) Salt based product (Salt). Further, two of the additive treatments were prepared with additional moisture: 6) Control with tap water addition (CON + w) and 7) LABmix with tap water addition (LABmix + w). The beans ensiled without additive showed elevated pH, butyric acid and ethanol concentrations and proportion of ammonia N in total N. Addition of water further decreased the fermentation quality. The LAB inoculants improved the fermentation quality of the beans compared to CON. The fermentation was effectively restricted when FA was used. Both LAB and chemical additives improved aerobic stability compared to CON and Salt was especially effective in improving aerobic stability. Vicine disappeared totally during the ensiling period and also convicine was effectively degraded. It seems that promoting microbial activity in the silo either by LAB inoculation or increased moisture promoted the degradation of convicine, while chemical additives decreased the degradation of it. Total and particularly soluble proanthocyanidins were also degraded during the ensiling period. Crimping and ensiling is an alternative preservation method for faba beans which eliminates the energy consumption and investments required for drying. In addition, benefits regarding the concentrations of bioactive compounds may be expected.